HUBUNGAN ANTARA PELAYANAN PENGELOLA TBM “SANGKA MAMBACO” DENGAN INTENSITAS KUNJUNGAN MASYARAKAT DI TAMAN BACA MASYARAKAT JORONG PASAR KECAMATAN LIMA KAUM KABUPATEN TANAH DATAR - Drajat, Zikri; Ismaniar, Ismaniar (Jurnal Family Education, 2023)
The research background is the low intensity of community visits to community reading gardens in Lima Kaum District. This is presumably because the services of the management of TBM "Sangka Mambaco" are not optimal. The research objectives were to 1) describe the TBM Management Services in Lima Kaum District, 2) describe the intensity of community visits to the Community Reading Park in Lima Kaum District, and 3) determine the relationship between TBM Management Services and the intensity of community visits in TBM Lima Kaum District. This research includes correlational quantitative research. The population in this study was the entire community who visited the Lima Kaum District, totaling 30 people. The total sampling technique is a technique for taking as many samples as the population. Researchers determine the research sample as much as 100% of the population. The data collection technique is a questionnaire, a data collection tool using a questionnaire which contains a list of statements or questions. The data analysis technique is the percentage and correlation formula Spearman Ro. The results showed that (1) the description of the service relationship between the TBM "Sangka Mambaco" management was not good, (2) the description of the intensity of visits by the TBM "Sangka Mambaco" community was still low (3) there was a significant relationship between the services of the TBM "Sangka Mambaco" manager and the intensity community visits in Lima Kaum District.